PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, STRES KERJA DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. SAMUDRA SINERGI JAYA DI SUKOHARJO - Mohamad Bayu Nugroho; Tri Ratna Pamikatsih (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The purpose of this study was to determine the effect of job satisfaction, organizational commitment, work stress and employee workload at PT Samudra Sinergi Jaya.Determination of the sample using the saturated sample method, out of 35 populations used for the sample of 24 respondents. The data sources used are primary and secondary data. The data collection method uses the distribution of questionnaires and the data analysis method uses data instrument tests, classical assumption tests and hypothesis testing. The test results show that partially the variables of job satisfaction, organizational commitment, work stress and workload have a positive and significant effect on the turnover intention of PT Samudra Sinergi Jaya employees. From the variables of job satisfaction, organizational commitment, work stress and workload have an influence of 73.4% and the remaining 26.6% is explained by other variables not included in this study